Differential gene expression of tumor-infiltrating CD8+ T cells in advanced versus early-stage colorectal cancer and identification of a gene signature of poor prognosis. Issue 2 (18th September 2020) - Saleh, Reem; Sasidharan Nair, Varun; Toor, Salman M; Taha, Rowaida Z; Murshed, Khaled; Al-Dhaheri, Mahmood; Khawar, Mahwish; Petkar, Mahir Abdulla; Abu Nada, Mohamed; Al-Ejeh, Fares; Elkord, Eyad
Abstract : Background: Cytotoxic CD8 + T cell-mediated response is the most important arm of adaptive immunity, which dictates the capacity of the host immune response in eradicating tumor cells. Due to tumor intrinsic and/or extrinsic factors, the density and function of CD8 + tumor-infiltrating lymphocytes (TILs) could be compromised, leading to poor prognosis and survival. Methods: Using RNA-Seq, transcriptomes of sorted CD3 + CD8 + TILs from treatment-naïve colorectal cancer (CRC) patients at advanced stages (III and IV) were compared with those from patients with early stages (I and II). A signature referred to as 'poor prognosis CD8 gene signature (ppCD8sig)' was identified and analyzed in The Cancer Genome Atlas CRC dataset. Scores for the ppCD8sig were calculated and classified as high, intermediate and low, and its prognostic significance was assessed using multivariate analysis and Cox proportional hazard model. Densities of CD3 + and CD8 + T cell infiltration in tumors from patients with high and low ppCD8sig scores were assessed by flow cytometry and immunostaining. Results: Genes related to epigenetic regulation and response to hypoxia were upregulated in CD8 + TILs from patients with advanced stages, while genes related to T cell activation, cell proliferation and cell cycle were downregulated. Patients with high ppCD8sig score had poorer disease-specific survival (DSS) and shorter progression-free interval (PFI). The ppCD8sig was an independent prognostic indicator for DSS (HR 1.83, 95% CI 1.40 to 2.38, p<0.0001) and PFI (HR 1.42, 95% CI 1.04 to 1.93, p=0.026). Additionally, patients with high ppCD8sig score were more likely to have advanced stages (χ 2 p<0.0001) and residual disease after primary therapy (χ 2 p=0.046). Patients with high ppCD8sig score had reduced levels of CD3 + and CD8 + TILs and low Immunoscores (IS), compared to patients with low ppCD8sig score. Conclusions: Our data provided insights into the altered regulation of biological mechanisms and signaling pathways in CD8 + TILs during CRC progression, and revealed a gene signature as an independent prognostic indicator. Patients with high ppCD8sig score had lower levels of TILs and low IS. These data further confirm the prognostic value of the identified ppCD8sig and potentially highlight its clinical relevance.